2019
DOI: 10.1007/s10658-019-01745-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of year, sampling month and grape cultivar on noble rot incidence, mycelial growth rate and morphological type of Botrytis cinerea during noble rot development

Abstract: The aims of this three-year study were firstly to investigate the effect of 3 years, three sampling months and two grape cultivars (cvs) on noble rot incidence in the field and on the mycelial growth rate of Botrytis cinerea isolates in vitro under three incubation temperatures, and secondly to show possible effects of years, sampling months and cultivars on eight morphological (four mycelial: M I-IVand four sclerotial: S I-IV) types of B. cinerea isolates incubated at 20°C. In addition, the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The key findings of our paper include that (1) most measured physical and chemical parameters changed predictably during the noble rot process; (2) sampling month during the long harvest period influenced several of these physico-chemical traits, and (3) while keeping to the main trends, cultivars often differed in some physical, chemical, and microbiological aspects [ 31 , 33 ]. In addition, the results largely corresponded to the botrytization phases previously defined based on visual criteria [ 10 , 28 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The key findings of our paper include that (1) most measured physical and chemical parameters changed predictably during the noble rot process; (2) sampling month during the long harvest period influenced several of these physico-chemical traits, and (3) while keeping to the main trends, cultivars often differed in some physical, chemical, and microbiological aspects [ 31 , 33 ]. In addition, the results largely corresponded to the botrytization phases previously defined based on visual criteria [ 10 , 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…B. cinerea is a common and widespread ascomycete fungus and necrotrophic pathogen attacking numerous different plant species (e.g., grape, tomato, kiwi fruit, strawberry and raspberry, herbaceous, shrub and tree species) [ 7 , 8 , 9 ]. Fournier et al [ 6 ] compared populations of B. cinerea associated with grey mold versus noble rot symptoms in various wine regions of France and showed that noble rot development was influenced by climate, cultivar, vintage, cultural practices, and berry microbiome [ 10 ]. The occurrence of noble rot is dependent mainly on microclimatic conditions [ 11 ]; however, there is a lack of information on the textural and microbial characteristics of the grape berries during the noble rot process.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, no development of the rotting process was observed in the berry flesh covered with grey mycelium. In the more dried-out bunches, some of the berries were covered with a pink coating that remained after the dried juice (Hegyi-Kalo et al, 2019). SEM observations revealed the exact details of the mycelial growth of B. cinerea.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, although anthocyanins are the main source of red color in strawberry fruit, the more intense red coloration of certain genotypes might be associated with a higher abundance of other phenolic compounds that reduce the susceptibility. Hegyi-Kaló et al (2019) observed that the inhibition of B. cinerea growth was more profound on grape berries with dark-skin color than on white-skinned berries that contain lower concentrations of phenolic compounds.…”
Section: Increased Red Coloration Is Associated With Lower Spoilage R...mentioning
confidence: 97%
“…Previous studies on B. cinerea spoilage in strawberry fruit have reported the effects of year, cultivar and the cultivar × year interaction on fruit spoilage (Hegyi-Kaló et al, 2019). Some of these studies reported that the variation of B. cinerea spoilage between years was more profound than genotypic differences within years (Chandler et al, 2006;Seijo et al, 2008).…”
Section: Spoilage Rates Of Strawberry Fruit Are Genotype-dependentmentioning
confidence: 99%